Problematika Mediasi di Pengadilan Agama Gorontalo dan Pengadilan Agama Limboto Tahun 2015 - Ahmad Faisal (Al-Mizan (e-Journal), 2016)
The integration of mediation in court practices, on the one hand intended to avoid the accumulation of cases, but on the other hand increase the burden of the judges. For that reason, it is understandable if the success rate is very small mediation divorce case. Paramediator limited time availability, lack of skills/skill mediator, lack of motivation and persistence finish the case, the absence of a mediator from outside the court registered a problematic instrument relating to the judge mediator. This condition presupposes the involvement of non-judge mediators, who have local knowledge base to engage in mediation cases. In fact, the regulations will it also looked very normative-procedural. In addition, this type of divorce case is rather complicated, especially if motivated by domestic violence, disharmony, the presence of third parties into its own problematic when mediated. But the most decisive is the parties who appeared since the beginning has been shut down to peace, making its implementation more complicated problems of mediation in Gorontalo Religious Court and Limboto Religious Court.